Tawarruq and Wa’d as main ingredients of Islamic structured investment: food for thought - Mustaffa Kamil, Nazrol Kamil (IIUM Press, 2020)
This article discusses in detail one example of an Islamic structured investment product. The said product is used as an illustration to highlight some issues deemed critical in the development of the wider Islamic finance space. The author humbly submits that convoluted structures, quite common in contemporary Islamic finance, are generally not healthy for the industry and its stakeholders. Opacity in financial dealings not only increases the cost of doing business, it makes risk assessment and management that much more challenging, to both transacting parties and regulators. Some additional perspectives related to the polemic on the practice of tawarruq are also offered. Finally, some thoughts on the widespread usage of wa’d as a somewhat indispensable tool in structuring contemporary Islamic financial instruments as well as the attitude towards risk inherent in structured products vis-à-vis a reasoned Islamic risk-return paradigm are deliberated upon.